Environmental, socioeconomic, maternal, and breastfeeding factors associated with childhood overweight and obesity in Ceará, Brazil: a population-based study - Rocha, Sabrina G. M. O. (2020)
Childhood obesity is now an epidemic in many countries worldwide and is known to be a multifactorial condition. We aimed to examine the relationship of environmental, socioeconomic, and nutritional factors with childhood overweight and obesity. We conducted a population-based cross-sectional study of children from 2 to 6 years of age in Ceará, Brazil. Children’s nutritional status was assessed by body mass index (BMI) Z scores categorized as overweight and obesity. Ordinal logistic regression models were used to assess the relationship between the factors with overweight and obesity. A total of 2059 children participated, of which 50.4% were male. The mean age was 46 17 months, with a prevalence of overweight and obesity of 12.0% (95% CI 10.7–13.6) and 8.0% (6.7–9.5), respectively. In multivariate analysis, the probability of childhood obesity increased as family income increased (adjusted hazard ratio (aHR) 0.6 (95% CI 0.37–0.95), p-value = 0.03). Moreover, families with fewer children had more than 30% fewer overweight children (aHR 0.68; 95% CI 0.48–0.96). Environmental, socioeconomic, and child nutritional factors were associated with overweight and obesity. The results provided could be used to design integrated interventions spanning from conception, or earlier, through the first years of life and may improve child nutritional outcomes.